Green Synthesis of Gold Nanoparticles using Peronema canescens Leaves Extract and Their Catalytic Performance for Dyes and Nitro Compounds - Falahudin, Aswin; Insin, Numpon; Yudha S, Salprima; Adfa, Morina (Universitas Jenderal Soedirman, 2023)
The most interesting and well-known research in the field of gold nanomaterials synthesis is the use of